An assessment of the translation-specificity of over-represented multi-word patterns in Swedish fiction texts translated from English - Nilsson, P-O (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This paper discusses in what sense an over-represented multi-word pattern in a corpus of translated texts can be said to be typical of translated text. The purpose of the discussion is to assess, from a quantitative as well as from a qualitative perspective, the status of translational collocation data retrieved through data-driven methods from a comparable and parallel aligned cor¬pus of English and Swedish original and translated texts. The study focuses on the explicitation of clausal relations in translations from English into Swedish. In some cases, lexical and grammatical contrast lead to explicita¬tion, but in others explicitation is due to different factors.